Women's Reproductive Health during COVID-19 (Journal of Chittagong Medical College Teachers' Association, 2021)
Background : Reproductive health of women is considered as the central feature of human development. A healthy child is one of the best gift of good female reproductive system ensuring the survivor off spring to withstand the changing global diverse situations. Even though now-a-days some organizations decided and are planning that teachers and parents should be involved as primary sex educators through friendship.This review article is aimed to design to provide and insight the update information and the relationship between women’s reproductive health and COVID-19 is necessary for optimum management of such condition.Methodology : In this narrative review, literature search done by using PubMed, Medline, Google Scholar and Cochrane date bases of systemic review and citation list of relevant publication.Conclusion : In the pandemic high risk situation it is necessary that health care teams to focus more on women’s mental health, domestic violence, sexual relationships, use of contraceptive methods and intending for child bearing. Providing virtual group educations and use of national media, could enhance the awareness of women’s reproductive health. Further study may reveal more clearly the various aspects of women’s reproductive health during COVID-19.JCMCTA 2021 ; 32 (2) : 3-7